Self-assessment of friendships and social inclusion of adults with intellectual disabilities - Fabris, Alisa; Bratković, Daniela; Žic Ralić, Anamarija (Specijalna edukacija i rehabilitacija, 2023)
Introduction. Persons with intellectual disabilities often experience difficulties in achieving interpersonal relations and social inclusion, which are important aspects of quality of life. Objectives. This paper aims to examine the perspective of people with intellectual disabilities on friendships and social inclusion and identify factors which influence their development, with the ultimate goal of defining recommendations for improving support. Methods. A qualitative research approach was chosen to gain insight into participants’ subjective experiences and views. For this purpose, an individual semi-structured interview was conducted with eight adults with mild and moderate intellectual disabilities. Results. Participants generally express satisfaction with their friendships and social involvement. They spend time with friends mostly in the centre where they are included in daily program. They especially emphasize the importance of the emotional support they receive from friends. In addition to activities in the daily centre, participants play sports, but most of their free time spend at home. The factors that negatively affect their social inclusion and friendships are overly protective relationship of parents, living conditions and their low motivation. The factors that promote both are parental support, use of social media and visiting different places in community. Conclusion. Although participants are mostly satisfied with their friendships and social inclusion, they also express different needs. Being included in daily centre has positive impact on developing friendships and social inclusion, but at the same time, it is necessary to offer inclusive contents in society and provide both formal and informal support in this area.
Keywords: friednship; social inclusion; intellectual disability; disability